Continuidad en la técnica de elaboración de moldes para el vaciado de plata en el área centro andina desde la época precolombina hasta la actualidad - Vetter Parodi, Luisa (2019)
In Precolumbian times, silversmiths used different casting techniques to make their metal works. One of them was casting with bivalve molds made with clay and organic temper. The same technique can be seen nowadays at San Pablo de Canchis, where Cuzco silversmiths made their works with similar techniques to those of Precolumbian times. In order to determine if there was a technology transfer between Precolumbian silversmiths and San Pablo's, we have analized molds from the Inca cemetery of Rinconada Alta, La Molina, in Lima, and also molds from San Plablo de Canchis, using scanning electron microscope and energy dispersive spectroscopy (SEM-EDAX), X ray fluorescence (XRF) and X ray diffraction (XRD).